Smoking Bans, Leisure Time, and Subjective Well-being - Cornelia Chadi (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
During 2007 and 2008 smoking bans were gradually implemented in all of Germany's sixteen federal states to prohibit smoking in bars, restaurants, and dance clubs. Aimed at reducing smoking and improving health, tobacco control policies are often controversially discussed as they entail potential side effects. We exploit regional variation to identify effects of smoking bans on life satisfaction and leisure time satisfaction. Difference-in-differences estimates reveal that predicted smokers who used to visit bars regularly are less satisfied with life and leisure time, following the enforcement of a smoking ban. We show that changes in use of leisure time likely explain these findings. On the contrary, predicted non-smokers who did not visit bars and restaurants frequently benefit from the smoking bans, as their satisfaction with leisure time increases. They show an increase in hours spent on free-time activities and are more likely to go out with smoking bans in effect.
Keywords: D62; I18; I31; J22; D62; I18; I31; J22; 330; Smoking bans; subjective well-being; leisure time; treatment effects